Thermocapillary actuation of a water droplet encapsulated in an oil plug - Jiao, Zhenjun (2012)
This paper reports the theoretical and experimental results of thermocapillary actuation of silicon oil plugs with encapsulated water droplet inside a capillary tube. The paper first describes the analytical models for this actuation concept. The model considers periodic actuation based on heat transfer in the capillary wall and the surface tension driven motion of the plug. In the experiments, both temperature field and plug motion were measured and evaluated. While the temperature field was measured by an infrared thermal tracer camera, the position of the plugs was automatically captured and evaluated with a CCD camera. Several interesting phenomena resulting from the interaction between surfactant modified silicone oil and water were observed. Different cases were observed and investigated: the water droplet partially wets the wall, the water droplet completely wets the wall, and the water droplet is encapsulated.